The effectiveness of development financing: A practitioner's perspective… - Olivier Lafourcade (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
The objective of the Chair in International Architecture of Development Finance (IADF) is to "reflect independently about what the global development finance system should become in light of the current international situation and the lessons learned from the experience of the past 60 years." Therefore, the IADF has initiated a series of studies on some of the important themes concerning the prospects for adjusting the organization and functioning of the international institutional apparatus. As part of the preparations for the June Summit on the theme of financing vulnerable countries, the IADF Chair has been led to adapt, accelerate and amplify its programme so as to make contributions on several themes that are crucial to the Summit' orientation.
Keywords: 330; International Architecture of Development Finance